Clinical Benefit of Tyrosine Kinase Inhibitors in Advanced Lung Cancer with EGFR‐G719A and Other Uncommon EGFR Mutations. (6th October 2020) - Sehgal, Kartik; Rangachari, Deepa; VanderLaan, Paul A.; Kobayashi, Susumu S.; Costa, Daniel B.
Abstract: : The optimal management of advanced non‐small cell lung cancer (NSCLC) with noncanonical epidermal growth factor receptor ( EGFR ) mutations (i.e., exon 19 deletion and exon 21 L858R) is constrained by the heterogeneous behavior of individual uncommon mutations and limited prospective clinical data in this setting. Despite encouraging results with osimertinib from a recently published phase II trial from South Korea, afatinib remains the only currently approved drug for patients with tumors harboring uncommon EGFR mutations (i.e., S768I, L861Q, and/or G719X). When used at the standard dose of 40 mg daily, afatinib is associated with significant rates of treatment‐related adverse events, leading to frequent dose reductions and treatment discontinuations. We report a case of a woman with advanced NSCLC harboring EGFR ‐G719A mutation treated with afatinib (at an off‐label pulse dose strategy that merits further evaluation in prospective studies) with sustained partial response for 20 months with manageable expected toxicities. Subsequent disease progression was mediated by off‐target pan‐EGFR inhibitor (including osimertinib)–resistant KRAS mutation and not by acquisition of EGFR ‐T790M. We further present the current state of evidence in the literature behind use of first‐, second‐, and third‐generation tyrosine kinase inhibitors and summarize the evolving spectrum of activity ascribed to osimertinib (and newer EGFR inhibitors with a more favorable therapeutic window and intracranial penetration) in this population of patients with advanced NSCLC and uncommon EGFR mutations. Key Points: Uncommon EGFR mutations characterize a heterogeneous group of patients with advanced non‐small cell lung cancer (NSCLC). Afatinib is the only currently U.S. Food and Drug Administration–approved drug for management of advanced NSCLC with uncommon EGFR mutations (S768I, L861Q, and/or G719X). Afatinib treatment at 40 mg daily is associated with high rates of adverse events and dose reductions; alternative strategies including pulse intermittent dosing should be evaluated prospectively. Osimertinib (with favorable safety profile and intracranial penetration) has shown promising results in this population in a phase II trial from South Korea; additional trials are ongoing. Abstract : This article presents the case of patient with advanced non‐small cell lung cancer harboring an EGFR ‐G719A mutation treated with afatinib and reviews the literature regarding the use of first‐, second‐, and third‐generation tyrosine kinase inhibitors in this patient population.